Expression of epithelial-mesenchymal transition markers E-cadherin and ZEB1 in colorectal cancer - I. A. Novikova; O. I. Kit (Исследования и практика в медицине)
Purpose of the study. Evaluation of expression of the epithelial-mesenchymal transition markers E-cadherin and ZEB1 in patients with stage II-IV colorectal cancer (CRC).Materials and methods. The study included operational material obtained from 299 patients aged 42–86 years (mean age 64.2±1.7 years) with stage II-IV CRC treated at National Medical Research Centre for Oncology in 2013-2017. Stage II CRC (T3-4 N0 M0 ) was diagnosed in 110 patients, stage III (T1-4 N1-2 M0 ) – in 88 patients, stage IV (T1-4 N0-2 M1 ) – in 101 patients. Polyclonal rabbit antibodies to ZEB1 (Biorbyt Ltd., UK) and mouse monoclonal antibodies to E-cadherin (Diagnostic BioSystems, USA) were used for an IHC analysis. The intensity and degree of tumor cell staining, percentage of stained tumor cells in the sample and the number of patients with positive and negative marker expression were determined. Groups were compared using the Mann–Whitney U test and the Pearson's chi-square test.Results. Positive expression of E-cadherin was found in 64.5 % (193 of 299 patients), ZEB1 – in 80.6 % (241 of 299 patients). The number of patients with E-cadherin-positive tumors statistically significantly decreased (χ2 =15.888 at p<0.001) from stage II to stage IV, while for ZEB1, on the contrary, it statistically significantly increased (χ2 =43.912 at p><0.001) from stage II to stage IV. The mean values of expression in positively stained cells were: in stage II – E-cadherin 55.3±6.8 %, ZEB1 43.0±5.9 %; in stage III – E-cadherin 38.4±5.8 %, ZEB1 77.0±5.5 %; in stage IV – E-cadherin 14.7±4.7 %, ZEB1 76.9±3.5 %. Significant differences were observed between the mean values of ZEB1 expression in stages III and IV compared to stage II, as well as between the mean values of E-cadherin expression in stages II and III compared to stage IV (p><0.05). No significant differences were found in the mean values of ZEB1 and E-cadherin expression in stages III and IV, II and III respectively.Conclusions. The study demonstrated statistically significant relationship between tumor stages and expression of E-cadherin and ZEB1 in the epithelial-mesenchymal transition. The loss of the E-cadherin expression in tumor cells of patients from stage II to stage IV and increased expression of ZEB1 in the studied groups were statistically significant (p<0.05).